Tax Socialization, Love of Money, and Taxpayer Compliance: The Role of Tax Awareness Mediation among Individual Taxpayers - Anisa Nursania; Ita Rakhmawati (Journal of Accounting Science, 2026)
General Background: Tax authorities around the world face ongoing challenges in optimizing revenue due to persistent taxpayer non-compliance. Spesific Background: Indonesia continues to face shortfalls in tax revenue targets, as reflected in a 16.72% decline recorded in August 2025, indicating that taxpayer compliance remains insufficient to support fiscal objectives. Knowledge Gap: The existence of inconsistencies in previous studies related to the socialization of taxation and love of money towards taxpayer compliance, and some previous studies still place the taxpayer awareness variable as an independent variable. Objective: This study aims to examine the effects of tax socialization and love of money on taxpayer compliance and to analyze the mediating role of taxpayer awareness in this relationship. Methods: This study used a quantitative approach with primary data sources. Samples were obtained through convenience sampling, while data collection was conducted through questionnaires and analyzed through multiple linier regression test. Results: Tax awareness mediates the effect of tax socialization on compliance, while love of money has no effect. Novelty: This study combines love of money and taxpayer awareness in a mediation model between tax socialization and compliance, expanding the focus from external factors to internal motivation. This approach also utilizes attribution theory to provide an additional analytical perspective in understanding taxpayer behavior. Implication: The findings indicate that taxpayer compliance can be improved by designing tax awareness campaigns that emphasize awareness, objectives, and benefits of taxation, as well as more targeted and interactive communication